Racial inequality, racial discrimination and obesity incidence in adults from the ELSA-Brasil cohort - Machado, Amanda Viana (2021)
Universidade Federal de Minas Gerais. Faculdade de Medicina. Programa de Pós-Graduação em Saúde Pública. Belo Horizonte, MG, Brasil.